Automatic college bell system - Shrikant and Priyanka Sharma, Sheenu Choudhary (International Journal of Scientific Research and Management (IJSRM), 2017)
The world over the decades has made considerable advancement in automation; automation is employed in every sector whether it is home or industry. Here a new and inexpensive design is being presented. This design finds a tremendous use at primary and secondary school levels as well as in colleges where the teaching sections can span over eight periods including breaks. The advantage of this design is that the bell rings at the start of each period without any human intervention to a great degree of accuracy and hence takes over the manual task of switching on/off the college bell with respect to time. It uses Real Time Clock (DS1307) which tracks the real time. The scheduled time results are compared with that of a clock, however, some drift is noticed, which is negligible. The microcontroller AT89S52 is used to control all the functions, it gets the time through the keypad and stores it in its memory. When this programmed time equals the real time then the bell is switched on via a relay for a predetermined time. The bell ringing time can be edited at any time, so that it can be reused again and again at normal class timings as well as at exam times. Also it can be made password protected so that no unintended person can operate this system except for the operator. For this a microcontroller has to be programmed using the C language or assembly language for controlling the circuit